Traditional Chinese Medicine for adolescent idiopathic scoliosis: a systematic review and meta-analysis - Li, Peng; He, Yue; Zhou, Jihe; He, Min (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the clinical effectiveness of Traditional Chinese Medicine (TCM) interventions—such as spinal manipulation, Daoyin exercises, acupuncture, and massage—in adolescents with idiopathic scoliosis, and to summarize structured treatment regimens for clinical reference.MethodsA systematic search was conducted in PubMed, Embase, Web of Science, CNKI, VIP, and Wanfang databases from inception to March 2024. Randomized controlled trials (RCTs) comparing TCM with conventional treatments in adolescent idiopathic scoliosis were included.ResultsTCM interventions—ranging from spinal manipulation and Daoyin corrective exercises to acupuncture and massage—were delivered 2–5 times per week over 4–12 weeks. Meta-analysis showed a significant reduction in Cobb angle (MD = −3.97, 95% CI: −4.24 to −3.71, p < 0.00001) and increased total effectiveness (OR = 4.42, 95% CI: 3.22–6.08, p < 0.0001). Egger's test and funnel plots showed no major publication bias. Subgroup analysis indicated consistent outcomes across different TCM techniques.ConclusionThis meta-analysis demonstrates that TCM interventions—particularly spinal manipulation, Daoyin exercises, acupuncture, and massage—are effective in improving both structural and clinical outcomes in AIS. A practical regimen of manual therapy (2–3 times/week), daily Daoyin exercise, and supportive acupuncture and massage over 12 weeks offers a safe, non-invasive alternative to bracing or surgery, with high patient compliance.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD42024589328.